Emotional and cognitive conflict resolution and disruptive mood dysregulation disorder in adolescent offspring of parents diagnosed with major depressive disorder, bipolar disorder, and matched healthy controls - Topal, Zehra; Demir, Nuran; Tufan, Evren; Tuman, Taha Can; Semerci, Bengi (Taylor and Francis Ltd., 2021)
Aims: Children of parents with mood disorders have an elevated risk for various psychopathologies. In this study rate of psychopathologies among adolescent offspring of parents with major depressive (MDDoff) and bipolar disorder (BDoff), including disruptive mood dysregulation disorder (DMDD) along with the offspring ability to resolve cognitive and emotional conflicts were evaluated. Method: 12–16 years old children of parents with MDD (n = 31, children= 36), BP (n = 20, children = 26) and controls (n = 25, children = 28) were enrolled. Children and parents were evaluated by using the Kiddie Schedule for Affective Disorders and Schizophrenia (K-SADS) and the Structured Clinical Interview for DSM-IV Axis I Disorders (SCID); respectively. The parents completed the Child Behavior Checklist (CBCL)-dysregulation profile. The Stroop test-TBAG form and emotional Stroop test were given out to evaluate conflict resolution ability. Results: The most common diagnoses among the whole sample were attention deficit and hyperactivity, separation anxiety and oppositional defiant disorders. Five cases (5.5%) of lifetime DMDD were found (three from MDDoff, the rest from BDoff). Completion times for the Stroop test-TBAG form were ranked as: BDoff > MDDoff > Hoff. In the emotional Stroop test, the BDoff responded significantly later and had significantly reduced correct responses. Conclusion: Rates of lifetime DMDD were similar in the MDDoff and BDoff groups. BDoff may experience greater difficulties in resolving cognitive and emotional conflicts.
Keywords: Cognitive Control; Emotional Control; Mood Disorder; High-Risk Offspring